Factors affecting the attachment of Treponema pallidum to mammalian cells in vitro. Issue 1 (February 1983) - Wong, G H; Steiner, B; Faine, S; Graves, S
Abstract : Attachment of Treponema pallidum (Nichols) to mammalian cells is probably the first step in the pathogenesis of syphilis. It may also be important for the multiplication of T pallidum in vitro. When factors affecting the attachment of T pallidum to mammalian cells in vitro were studied significantly greater numbers of treponemes were found to attach to baby rabbit genital organ (BRGO) cells than to five other mammalian cell lines. When attached to BRGO cells T pallidum survived longer in vitro than unattached treponemes. Eagle's minimal essential medium was superior to three other culture media in increasing attachment and maintaining the survival of treponemes. Dithiothreitol (0.25-1.0 mmol/l) had no effect on the attachment of T pallidum to BRGO cells. Anaerobic conditions were superior to microaerophilic conditions, and the latter were superior to aerobic conditions for the attachment and survival of T pallidum to BRGO cells. Within the range of concentrations tested the number of treponemes attached to the BRGO cells was directly dependent on the concentrations of viable treponemes in the inoculum. Greater numbers of treponemes attached to actively metabolising BRGO cells than to quiescent or slowly growing cells.